Bi-directional crosstalk between lymphatic endothelial cell and T cell and its implications in tumor immunity - Angeli, Veronique; Yeo, Pin K. (Frontiers in Immunology, 2017)
Lymphatic vessels have been traditionally considered as passive transporters of fluid and lipids. However, it is apparent from recent literature that the function of lymphatic vessels is not restricted to fluid balance homeostasis but also extends to regulation of immune cell trafficking, antigen presentation, tolerance and immunity, all which may impact the progression of inflammatory responses and diseases such as cancer. The lymphatic system and the immune system are intimately connected, and there is emergent evidence for a crosstalk between T cell and lymphatic endothelial cell (LECs). This review describes how LECs in lymph nodes (LNs) can affect multiple functional properties of T cells and the impact of these LEC-driven effects on adaptive immunity and, conversely, how T cells can modulate LEC homeostasis. The significance of such crosstalk between T cells and LECs in cancer will also be discussed.